Oxidation behaviour of NiAl intermetallics with embedded Cr and Mo. (December 2020) - Geramifard, Golnar; Gombola, Camelia; Franke, Peter; Seifert, Hans J.
Highlights: The oxidation of a coarse composite of a NiAl alloy with an embedded Cr rod was examined for the first time. A mixed layer of oxides was formed at the interface of NiAl and Cr. Composition of the mixed oxide changed from almost pure Cr2 O3 to Al2 O3 -rich from the outer to the inner layer of the oxide. Contrary to NiAl-Mo composites, the oxides formed on NiAl-Cr were to a certain extent protective. Abstract: The isothermal oxidation of directionally solidified NiAl-34Cr and NiAl alloys with embedded Cr bar and Mo wire were studied in a thermobalance at 800 °C, 1200 °C and 1300 °C for 50 h (Ar/ 13 vol.% O2 ). NiAl-Cr showed formation of a continuous Al2 O3 -Cr2 O3 solid solution in the vicinity of the interface of NiAl and Cr in which the composition changed from almost pure Al2 O3 near the metal matrix to almost pure Cr2 O3 near the gas surface. DS NiAl-34Cr showed more spallation compared to NiAl-Cr. In case of NiAl-Mo, a weight loss was observed due to formation of volatile oxides.